Strategic Management of Islamic Boarding Schools in Developing Students' Achievements in The Qur’an Recitation Competition - Siti Aisyah; Abd. Haris; M. Fahim Tharaba (Islamic Education Management Study Program, Faculty of Tarbiyah, Sunan Drajat Islamic Boarding School Institute, Lamongan, East Java, Indonesia., 2026)
Pesantren as an Islamic educational institution has a strategic role in producing superior human resources, but not all pesantren are able to consistently produce students' achievements, especially in the Musabaqah Tilawatil Qur’an (MTQ) competition. This indicates the importance of management based on planned and sustainable strategic management. This study aims to analyze the pesantren's strategic management in developing students' achievements in the MTQ competition. The study uses a qualitative approach with a multi-site study design at Pondok Pesantren Madrasatul Qur’an Tebuireng Jombang and Pondok Pesantren Walisongo Cukir Jombang. Research subjects included caretakers, supervisors, and students, with data collection techniques in the form of in-depth interviews, participatory observation, and documentation studies. Data analysis uses an interactive model through data reduction, data presentation, and drawing conclusions, as well as validity testing through source and technique triangulation. The research results indicate that both pesantren implement strategic management comprehensively through strategic environmental analysis, strategy formulation based on pesantren values, implementation of MTQ development programs integrated into the education system, as well as continuous evaluation through program monitoring and improvement. The difference in strategy lies in the institutional approach and the pattern of technical development tailored to the characteristics of each pesantren. This study contributes to the development of Islamic education management studies by offering a conceptual model of pesantren strategic management based on Qur'anic achievement built on two distinct, empirically grounded strategic patterns a specialization-based pathway centered on branch-specific talent mapping at Madrasatul Qur’an Tebuireng, and a habituation-based pathway centered on collective discipline and structured daily routine at Walisongo Cukir, and provides practical implications for the continuous improvement of MTQ development quality.